Revision of the Overresected Nasal Tip Complex - Davis, Richard E. (Facial Plastic Surgery, 2012)
Tip deformities resulting from previous nasal surgery range from mild to profound. For the mild deformity, morbidity is low and successful correction is usually achieved with a modest and targeted surgical adjustment. However, for the profound deformity, overt cosmetic deformities and corresponding functional impairment are the byproducts of severe derangements in skeletal architecture. Hence, for the severely damaged nasal tip, a complex surgical revision in which the decimated nasal tip framework is reconstructed with autologous cartilage grafts is essential. However, rebuilding the decimated nasal tip is a challenging and risky procedure that is best left to the seasoned rhinoplasty specialist. Careful assessment of the previously operated tissues, combined with an accurate cosmetic analysis, must be juxtaposed with the patient's cosmetic desires to derive an individualized and effective treatment plan. Atraumatic soft tissue technique, combined with a strategic yet balanced and judicious application of graft material, often culminate in satisfactory surgical outcomes. Proper assessment, technical skill, and sound clinical judgment are all critical ingredients in successful restoration of the surgically compromise nasal tip.
Keywords: revision rhinoplasty; cephalic trim; overresected tip; sidewall tensioning; septal extension graft